Analysis Of The Implementation Of Marketing Mix On Customer Satisfaction Of Shopee - Febiana Rainy Hidayat; Sholikhah Sholikhah; Dewi Agustin Pratama Sari (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to find out how the marketing mix is ​​applied to consumer satisfaction on the Shopee platform in DKI Jakarta. The sample used in this research was 117 respondents with the criteria of being at least 15 years old, residing in DKI Jakarta and using the Shopee platform. This research uses four dimensions, namely product, price, promotion and place. This research uses descriptive analysis methods, Customer Satisfaction Index, Importance Performance Analysis and Gap Analysis. The results of the research show that implementing the marketing mix can provide satisfaction to Shopee platform consumers in DKI Jakarta. Based on the Importance Performance Analysis, there are three things that need to be improved, that is price with product quality, promotional safety so that there is no manipulative behavior and accuracy in product delivery. Based on Gap Analysis, it shows that the product and promotion dimensions need to be improved.